Energy‐resolved small‐angle neutron scattering from steel. Issue 2 (10th February 2017) - Oba, Yojiro; Morooka, Satoshi; Ohishi, Kazuki; Suzuki, Jun-ichi; Takata, Shin-ichi; Sato, Nobuhiro; Inoue, Rintaro; Tsuchiyama, Toshihiro; Gilbert, Elliot Paul; Sugiyama, Masaaki
Abstract : A new analysis technique for energy‐resolved small‐angle neutron scattering is proposed. The precipitate dimensions in steel determined from fitting the observed neutron attenuation spectra agree with those calculated from conventional fitting of the corresponding small‐angle neutron scattering profiles. Abstract : Recent progress of pulsed neutron sources has enabled energy‐resolved analysis of neutron attenuation spectra, which include information on neutron scattering. In this study, a new analysis technique for small‐angle neutron scattering (SANS) is demonstrated. A clear difference is observed in the neutron attenuation spectra between steels with different nanostructures; this difference can be understood as arising from attenuation due to SANS. The neutron attenuation spectra calculated from the corresponding SANS profiles agree well with the experimentally observed attenuation spectra. This result indicates that measurement of neutron attenuation spectra may enable the development of a novel experimental technique, i.e. energy‐resolved SANS.